UPAYA PENINGKATAN LITERASI KESEHATAN REPRODUKSI DALAM PENCEGAHAN KEKERASAN DAN INFEKSI MENULAR SEKSUAL PADA SISWA SMA BATIK 1 SURAKARTA - Izzatul Arifah; Regita Azzahra Prase (Universitas Muhammadiyah Surakarta, 2026)
Adolescents are at risk of experiencing reproductive health problems such as sexual violence and sexually transmitted infections. Good reproductive health literacy can influence adolescents to engage in behaviors that maintain reproductive health. Based on a situational analysis at SMA Batik 1 Surakarta, it was found that no reproductive health education had been conducted previously. This school also has no extracurricular activities related to reproductive health. Interviews with students at Batik 1 High School found that the majority of students only seek information about reproductive health when they experience problems and immediately trust the information they find on the internet. The goal of this community service program is to increase knowledge about sexual violence and sexually transmitted infections and to improve the reproductive health literacy of students at Batik 1 Vocational School in Surakarta. The community service method involved providing education through audiovisual media and demonstrations to 33 10th-grade students at Batik 1 High School in Surakarta. The results of the activity show that students have increased their knowledge about the prevention of sexual violence and STIs after receiving education. Students now also understand that not all information on the internet about reproductive health is accurate and have learned how to verify its accuracy. Students are also motivated to seek reproductive health information from reliable sources regularly. It is hoped that students who have received this education can act as peer educators and share the information they have received with their friends and family